El derecho a la libertad sexual de los adolescentes y la relevancia del consentimiento en los delitos de estupro. - Reino Saulag, Lizeth Clariza (2023)
The right to sexual freedom in adolescents is no longer a taboo as it was in the last century, today adolescents have the ability to decide about their life and sexual reproduction, this right is not only supported in the constitution of the Republic of Ecuador, but also in international instruments; in this sense, the following investigative work seeks to identify the relevance of the consent of adolescents in the crimes of rape, considering that this crime is of private exercise of the action, where without the intervention of the prosecutor, they are the parents of the minor, together with their lawyers the main promoters of the cause. For this purpose and based on its legal significance, which has even led to the pronouncement of the highest constitutional court in its judgment No. 13-18 CN/21, the relevance of consent in crimes where both parties involved are minors is analyzed, however, departing from said sentence, an analysis is carried out considering that said consent, in the specific crime of rape, may well harm a person of legal age, if said consent has been granted freely, voluntarily and without any type of force or intimidation. For this purpose and based on qualitative research and through historical logical, legal, doctrinal and comparative methods and with a mixed approach, the concepts and characteristics of the right to sexual freedom of adolescents are analyzed together with the relevance of consent in the crime of rape, culminating in a field investigation where justice operators and lawyers in free practice have allowed me to obtain information regarding the scope that the consent of adolescents should have in the resolution of a process.